Propuesta para la creación de un departamento comercial para el consultorio empresarial del programa de Administración de Empresas en la sede Bogotá (2024)
This work addresses the development of a proposal for the creation of a Commercial Department for the Business Consultancy of the Business Administration program at the Antonio Nariño University, Bogotá headquarters. This work arises with the objective of providing the business consulting office with an organizational structure that allows strengthening its functions and effective relationships with the academic and business community.